Once Upon a Christmas Dreary in the Lab of Shakhashiri (1982)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1982 lecture includes experiments demonstrate the properties of gases and liquids (methane, nitrogen, oxygen), combustion, chemiluminescence, crystallization, and acids and bases. Appearing to help with the demonstrations are Santa Claus; Bucky the Badger, the UW mascot; David Cronon, Dean of the College of Letters and Science; and UW Chemistry professors Fred Juergens and Vince Genna. This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself.
Keywords: Chemistry--Experiments; Christmas; Lectures; Science--Study and teaching; Liquid nitrogen; University of Wisconsin--Madison; Santa Claus (Fictitious character)